The Impact of Physical And Non-Physical Work Environment On Employee Productivity - Recky; Nazaruddin; Widyawati (Journal of Business and Management Inaba, 2024)
The objective of this study is to evaluate the influence of the physical and non-physical work environment on employee productivity within the Social and Community Welfare Section of Indragiri Hilir Regency. The research method employed was quantitative. The population under investigation was all civil servants and contract employees in the Social and Community Welfare Section, a total of 32 individuals, with a census sampling technique. Data collection was conducted using questionnaires, while data analysis was performed with the use of SPSS software. The results demonstrated that the physical and non-physical work environment exerts a positive influence on employee productivity.